AS03-Adjuvanted, Very-Low-Dose Influenza Vaccines Induce Distinctive Immune Responses Compared to Unadjuvanted High-Dose Vaccines in BALB/c Mice - Yam, Karen K.; Gupta, Jyotsana; Winter, Kaitlin; Allen, Elizabeth; Brewer, Angela; Beaulieu, Édith; Mallett, Corey P.; Burt, David S.; Ward, Brian J. (Frontiers in Immunology, 2015)
During the 2009-2010 influenza pandemic, an adjuvanted, dose-sparing vaccine was recommended for most Canadians. We hypothesize that differences exist in the responses to AS03-adjuvanted, low antigen (Ag) dose versus unadjuvanted, full-dose vaccines. We investigated the relationship between Ag dose and the oil-in-water emulsion Adjuvant System AS03. BALB/c mice received two IM doses of AS03A or AS03B with exaggerated dilutions of A/Uruguay/716/2007 H3N2 split virion vaccine Ag. Immune responses were assessed three weeks after the booster. Unadjuvanted ‘high’ (3µg) and low dose (0.03µg-0.003µg) vaccines generated similar serum antibody titers and cytokine secretion patterns in restimulated splenocytes. Compared to unadjuvanted ‘high-dose’ vaccination, both AS03A and AS03B-adjuvanted low-dose vaccines tended to elicit higher serum antibody titers, broader induction of cytokine secretion and generated more influenza-specific antibody secreting cells and cytokine-secreting CD4 and CD8 T cells in splenocytes. We show that varying Ag and/or AS03 dose in this influenza vaccination mouse model can strongly influence both the magnitude and pattern of the immune response elicited. These findings are highly relevant given the likelihood of expanded use of adjuvanted, dose-sparing vaccines and raise questions about the use of ‘standard’ doses of vaccines in pre-clinical vaccine studies.